Pembelajaran Dengan Teknologi Classroom dan Aplikasi Zoom di Sekolah Dasar Negeri 51 Kota Bengkulu - Marhalim; Ridho Ikhlasul; Teguh Wibowo; Yoga; Angga Saputa; Achmad Fahry (Program Studi Administrasi Fakultas Ilmu Sosial dan Ilmu Politik Universitas Muhammadiyah Bengkulu, 2021)
During the pandemic, the problem faced by SDN 51 In Bengkulu was the process of face-to-face learning that became hampered. The teaching activities at SDN 51 Kota Bengkulu have not used IT in its entirety / manual by being picked up by the student's guardian whether it is assignments and or the return of the assignment itself. One of the approaches that can be done for learning is to use media that can be used for teachers and students is information technology with e-learning model. The research was conducted by SDN 51 Kota Bengkulu, teachers can organize content, create classes, fill in some content and access learning using classrooms and sisw can access existing content that has been prepared, and teachers at SDN 51 Bengkulu can create online learning classes via zoom meeting